Optimization Formula Of Kolang-Kaling (Arenga Pinnata.) Peel-Off Gel Mask With Combination Pva - Cmc Na As Gelling Agent On Simplex Lattice Design - Martha Cahyani, Intan; Hanhadyanaputri, Eka Susanti; Wulan , Ariani Hesti; Sulistyarini, Indah (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2025)
Kolang-kaling fruit in topical preparations increase its effectiveness as an antioxidant. The peel-off gel mask is as an effective topical preparation for skin health and user comfort. Its formulation is determined by quality parameters, particularly forming a plastic film of PVA and CMC Na as polymers. This study aims to determine the effect of these combination and the ratio of both concentrations based on the physical characteristics and IC50 value. The optimization on the simplex lattice design was obtained in 8 runs with PVA concentrations (10% -15%) and CMC Na (0.5% -5.5%). The pH value, spreadability, adhesion, drying time, and IC50 were used as parameters to determine optimal formula. The results showed that the difference in PVA and CMC Na concentrations had a significant effect on all optimization parameters (p-value <0.05) and the lack of fit for each replication was not significant (p-value> 0.05). The optimal formula obtained PVA concentration of 14.97% and CMC Na 0.53% with a predicted pH of 5.55; adhesion of 6.63 seconds; spread power of 20.34 cm; drying time of 18 minutes, and IC50 of 25.5 ppm (desirability of 0.954), which is not significantly different from the observation results indicating the optimization is valid.